Conceptualizing Spiritual Value Internalization in Pesantren Education: the Role of the Suluk Tradition - Yunita Sari; Marzuki Abubakar; Teuku Zulkhairi (Ta'dib, 2026)
This study stems from the limitations of existing research on the internalization of spiritual values in pesantren education, which has tended to be descriptive and normative in nature and has not yet been formulated within a clear pedagogical framework. The purpose of this study is to formulate a concept regarding the process of internalizing spiritual values through suluk tradition at the Babussalam Pesantren in Aceh Singkil, with a focus on the Aliyah level as a transitional phase toward the spiritual and moral independence of the students. This study employs a qualitative approach using a case study design. Data collection was conducted through participatory observation, in depth interviews with teachers and students, and document analysis. Based on the results of the study, it was found that the internalization of values occurs through a structured pedagogical process comprising three main stages: cognitive transformation through normative instruction, the formation of social-habitual patterns through daily practices and interactions, and spiritual consolidation through suluk practices as a phase of intensive reflection. Within this framework, suluk functions as a pedagogical-spiritual mechanism that integrates the understanding of values and the habituation of behavior into the students’ intrinsic consciousness, thereby allowing values to develop into a relatively autonomous inner orientation. This process follows a spiral pattern, beginning with the stage of understanding, moving toward habituation, and culminating in integration through a series of structured spiritual experiences. Theoretically, this study contributes by offering an integrative model of value internalization in pesantren education that positions spiritual consolidation as a key dimension in strengthening Islamic character.